2016
DOI: 10.1002/jbm.b.33632
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of in situ forming anionic hydrogel as vitreous substitutes

Abstract: The natural vitreous is a biological hydrogel consisting primarily of a collagen and anionic hyaluronate. It is surgically removed in many ocular diseases and replaced with fluids, gases, or silicone oils. We have been interested in developing synthetic hydrogels as vitreous substitutes. In this study, we combined the stiffness and hydrophobicity of polymethacrylamide (PMAM) and the anionic nature of poly-methacrylate (PMAA) to make copolymers that would mimic the natural vitreous. We used bis-methacryloyl cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…The thiol content of the poly(MAM-co-MAA-co-BMAC) copolymer was 2% (mol) from NTSB assay and 1 HNMR. Liang et al [17] showed that the poly(MAM-co-MAA-co-BMAC) with 2% (mol) thiol cross-linker and a methacrylate content of 20% (mol) was biocompatible on ocular epithelial cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thiol content of the poly(MAM-co-MAA-co-BMAC) copolymer was 2% (mol) from NTSB assay and 1 HNMR. Liang et al [17] showed that the poly(MAM-co-MAA-co-BMAC) with 2% (mol) thiol cross-linker and a methacrylate content of 20% (mol) was biocompatible on ocular epithelial cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The poly (MAM-co-MAA-co-BMAC) (CoP) was synthesized by free radical polymerization of MAM, MAA and BMAC as described in detail by Liang et al [17]. The disulfide and thiol content in the copolymer was determined by the NTSB assay as used for gellan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the conventional free-radical polymerization, we were able to obtain copolymers with a molecular weight ( M n = 194 kDa) that, according to our previous work, is suitable for making hydrogels. 37 The thiol content (5.0–5.1 mol %), which was measured by a 2-nitro-5-thiosulobenzoate (NTSB) assay, was very close to the feed ratio (5.0 mol %), suggesting stoichiometric incorporation of thiol groups into the copolymer. The content of AMPS (20.6 mol %) was also close to the feed ratio (20 mol %), as determined by 1 H NMR.…”
Section: Resultsmentioning
confidence: 84%
“…The use of redox-active cross-links in this system facilitates injectability. 24 Using swelling equilibrium, rheology, and dynamic light scattering, we show that this combination, inspired by the major components of the natural vitreous, leads to synthetic materials which closely resemble the polymer volume fraction, shear modulus, elastic diffusion, and friction coefficient of the natural tissue.…”
Section: ■ Results and Discussionmentioning
confidence: 97%